2017
DOI: 10.1159/000481194
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Cardiac Angiosarcoma Associated with Disseminated Intravascular Coagulation with Nab-Paclitaxel: A Case Report and Review of the Literature

Abstract: Angiosarcoma of the heart is an uncommon soft tissue sarcoma. A few cases of disseminated intravascular coagulation (DIC) associated with angiosarcoma occurring in various organs, but not the heart, have been reported. Although taxane is commonly used in the treatment of metastatic angiosarcoma, data on the efficacy of nab-paclitaxel for angiosarcoma are limited. Here, we report probably the first case of a patient with primary cardiac angiosarcoma with coexisting DIC who was successfully treated with nab-pacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Only a few case reports mention anticoagulant therapies for DIC associated with angiosarcoma. Honda et al ( 7 ) reported the first case of a patient having primary cardiac angiosarcoma with coexisting DIC who was successfully treated with nab-PTX. This patient's DIC, treated with transfusion of fresh-frozen plasma and recombinant thrombomodulin-α (used for 6 days), improved shortly after the initiation of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few case reports mention anticoagulant therapies for DIC associated with angiosarcoma. Honda et al ( 7 ) reported the first case of a patient having primary cardiac angiosarcoma with coexisting DIC who was successfully treated with nab-PTX. This patient's DIC, treated with transfusion of fresh-frozen plasma and recombinant thrombomodulin-α (used for 6 days), improved shortly after the initiation of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[18] There are 3 cases reported of treating cardiac angiosarcoma with paclitaxel to good effect, from partial response to complete remission of primary tumor and distal metastasis but unfortunately it was not work in our patient. [1921] Ifosfamide is a broad used chemotherapy drug in angiosarcoma, combining with doxorubicin achieved a well effect was reported and epirubicin, another anthracycline drug, always combined with ifosfamide as chemotherapy regimen for soft-tissue sarcoma. [22] Endostatin is a wide spectrum tumor angiogenesis inhibitor, with slight side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Others such as chemotherapy or radiotherapy were effective only in sporadic cases. [1921] In this case, we aimed to discuss the effect of ifosfamide and epirubicin (IE) plus recombinant human endostatin (rh-endostatin) following palliative surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, tumor progression led to worsening of DIC. While treatment of DIC is usually targeted to the underlying cause, challenges arise when there is no available treatment option for the underlying cause [ 11 ].…”
Section: Introductionmentioning
confidence: 99%